The PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN GREEN FISHBALL DI HAMADI, KOTA JAYAPURA,PAPUA - Tomasila, Loepold Arthur (Pattimura University, 2024)
Wife has an important role in helping the family economy. Hamadi village, Subdistrict South Jayapura, Jayapura City is one of Village that has a fishing community. Problems that occur are not yet available business institutions in the community that can coordination fish processing business activities and Causing a lack of motivation and innovation as well as community creativity in developing processed fish products. This happened to one of the fishery business groups is POLAKSHAR Mama Papua, where processed fishery products are only made into smoked fish simply. The Participatory Rural Appraisal (PRA) approach was used in this activity.The community has a large role to implementing the proses and can make processed fishery products, namely meatballs that use tuna meat by add Green color from Moringa leaves with womb β-karoten that have functional properties as antioxidant, and can improve income and can managed well in a book keeping